2014
DOI: 10.1371/journal.pone.0105983
|View full text |Cite
|
Sign up to set email alerts
|

Hypoalbuminemia Is a Strong Predictor of 30-Day All-Cause Mortality in Acutely Admitted Medical Patients: A Prospective, Observational, Cohort Study

Abstract: ObjectiveEmergency patients with hypoalbuminemia are known to have increased mortality. No previous studies have, however, assessed the predictive value of low albumin on mortality in unselected acutely admitted medical patients. We aimed at assessing the predictive power of hypoalbuminemia on 30-day all-cause mortality in a cohort of acutely admitted medical patients.MethodsWe included all acutely admitted adult medical patients from the medical admission unit at a regional teaching hospital in Denmark. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 11 publications
6
94
0
6
Order By: Relevance
“…This was true of a single measurement as previously demonstrated3 13 14 and of an albumin trend. Importantly, the likelihood of mortality was predicted by the extent of a decrement in albumin over a number of days.…”
Section: Discussionsupporting
confidence: 75%
“…This was true of a single measurement as previously demonstrated3 13 14 and of an albumin trend. Importantly, the likelihood of mortality was predicted by the extent of a decrement in albumin over a number of days.…”
Section: Discussionsupporting
confidence: 75%
“…The results of this study could potentially lead to novel treatment strategies for severely malnourished children. For example, numerous studies have shown that hypoalbuminemia is strongly associated with increased mortality in critically sick patients [59].…”
Section: Discussionmentioning
confidence: 99%
“…3 Normally, albumin has a long half-life (15-19 days), but the plasma albumin can rapidly fall by 10-15 g/l in 3 to 5 days in critically ill patients. 4 www.jmscr.igmpublication. The inflammatory process can decrease the synthesis increase of albumin and increase its breakdown.…”
Section: Introductionmentioning
confidence: 99%